Warfarin in the treatment of refractory chronic cluster headache: a case report and review in therapeutic options - Boone, Dayany Leonel; Barreto, Emanuelle Ferreira; Parreira, Felipe Sales; Campos, Henrique Carneiro de; Silva, Lucas Roquim e (Headache Medicine, 2022)
Cluster headache is the most common of trigeminal autonomic cephalalgia, with variable prevalence. It can be episodic or chronic, with few remission and high therapeutic failure. The case refers to a 55-year-old female patient, hypertensive and diabetic, with a history of migraine without aura with pain management. In 2014, the patient began to present a new headache pattern, with a diagnosis of Chronic Cluster Headache. Pain management to nasal sumatriptan as an acute treatment. For the prophylactic treatment, she presented therapeutic failure to several medications, with pain management with the use of warfarin. Associated with valproic acid to control migraine. There are few cases described in the literature about the use of warfarin, and its mechanism is still unclear. Warfarin was a key drug, with more than a 50% reduction in attack control. There is a need for more clinical trials randomly that support it. Cluster headache has peculiar clinical diagnosis, being increasingly well recognized and diagnosed. Knowledge and institution of treatment can significantly improve the quality of life of patients, helping to recover the functionality of patients affected by treatment failure.